Kinerja Petugas Klinik Voluntary Counseling and Testing (VCT) HIV-AIDS di Gorontalo - Mohamad, Sabrina Nadjib; Firman, Muhammad Jihad; Arda, Zul Adhayani; Una, Mar’atuljannah (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
As a preventive service, Voluntary and Counseling Testing (VCT) serves as the first gateway in the HIV/AIDS case management system, providing information, support, care, and treatment. VCT implementation is based on five international principles known as the 5Cs: informed consent, confidentiality, counseling, accurate test results, and linkage to follow-up care, treatment, and prevention services. This study aims to describe the performance of staff in VCT clinics based on confidentiality and counseling components. This study employed an observational study with a descriptive approach, utilizing a Mixed-Methods design. Data were collected through structured questionnaires administered to 31 respondents from an exhaustive sample, direct observation at the clinic, and in-depth interviews with VCT clinic staff and key informants. The results showed that 18 respondents (58.1%) consistently implemented confidentiality or guaranteed the confidentiality of patient data. Respondents who consistently counseled patients were 19 respondents (61.3%), and 16 of them (51.6%) consistently provided information, conducted risk assessments, and responded to clients' emotional needs during pre- and post-test counseling. VCT clinic staff in Gorontalo demonstrated good performance and competence in providing services and counseling to patients (83.9%). Recommended improvements include regular training and knowledge enhancement, provision of psychosocial support for staff, and enhancements to clinic facilities and infrastructure.